Autoimmune encephalitis in psychiatric institutions: current perspectives - Bost C; Pascual O; Honnorat J (Neuropsychiatric Disease and Treatment, 2016)
Chloe Bost,1–3 Olivier Pascual,2,3 Jérôme Honnorat1–3 1French Reference Center of Paraneoplastic Neurological Syndrome, Hospices Civils de Lyon, Hôpital Neurologique, Bron, France; 2Synatac Team, NeuroMyoGene Institut, INSERM U1217/CNRS UMR5310, Lyon, France; 3University Claude Bernard Lyon 1, Lyon, France Abstract: Autoimmune encephalitis is a rare and newly described group of diseases involving autoantibodies directed against synaptic and neuronal cell surface antigens. It comprises a wide range of neuropsychiatric symptoms. Sensitive and specific diagnostic tests such as cell-based assay are primordial for the detection of neuronal cell surface antibodies in patients’ cerebrospinal fluid or serum and determine the treatment and follow-up of the patients. As neurological symptoms are fairly well described in the literature, this review focuses on the nature of psychiatric symptoms occurring at the onset or during the course of the diseases. In order to help the diagnosis, the main neurological symptoms of the most representative synaptic and neuronal cell surface autoantibodies were detailed. Finally, the exploration of these autoantibodies for almost a decade allowed us to present an overview of autoimmune encephalitis incidence in psychiatric disease and the general guidelines for the management of psychiatric manifestations. For the majority of autoimmune encephalitis, the prognosis depends on the rapidity of the detection, identification, and the management of the disease. Because the presence of pronounced psychiatric symptoms drives patients to psychiatric institutions and can hinder the diagnosis, the aim of this work is to provide clues to help earlier detection by physicians and thus provide better medical care to patients. Keywords: neuroimmunology, autoantibodies, organic psychosis, dementia, schizophrenia